2022
DOI: 10.1111/jch.14455
|View full text |Cite
|
Sign up to set email alerts
|

Current apparent treatment‐resistant hypertension in patients undergoing peritoneal dialysis: A multi‐center cross‐sectional study

Abstract: Apparent treatment-resistant hypertension (aTRH) is the most commonly used term to report resistant hypertension (RH) and is considered as a common problem in dialysis population. However, few reports have focused on peritoneal dialysis (PD) hypertensive patients. The authors conducted a multi-center cross-sectional study involving 1789 PD patients from nine centers in Guangdong, China. The prevalence of aTRH was estimated by home blood pressure (BP) monitoring. Evaluating drug adherence through Eight-item Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“… 6 , 7 Hypertension is one of the most important risk factors for cardiovascular morbidity and mortality, especially stroke, ischemic heart disease, chronic kidney disease (CKD), congestive HF, aortic aneurysm, and peripheral arterial disease (PAD). 8 , 9 , 10 Compared with the controlled hypertension, the risk of resistant hypertension in all‐cause mortality, cardiovascular mortality, and non‐fatal stroke increased significantly. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 7 Hypertension is one of the most important risk factors for cardiovascular morbidity and mortality, especially stroke, ischemic heart disease, chronic kidney disease (CKD), congestive HF, aortic aneurysm, and peripheral arterial disease (PAD). 8 , 9 , 10 Compared with the controlled hypertension, the risk of resistant hypertension in all‐cause mortality, cardiovascular mortality, and non‐fatal stroke increased significantly. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Hypertension is one of the most important risk factors for cardiovascular morbidity and mortality, especially stroke, ischemic heart disease, chronic kidney disease (CKD), congestive HF, aortic aneurysm, and peripheral arterial disease (PAD). [8][9][10] Compared with the controlled hypertension, the risk of resistant hypertension in all-cause mortality, cardiovascular mortality, and non-fatal stroke increased significantly. 11,12 The results of the REACH trial show that in patients with the entire atherosclerotic disease spectrum, whether it is currently asymptomatic, in the subclinical or has been identified in patients with single or multiple vascular disease, resistant hypertension caused varying degrees of adverse results.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to medication adherence, a recent study in China reported that patient adherence was positively correlated with perceived necessity and negatively correlated with concern [46]. Among 283 PD hypertensive patients who completed the MMAS-8 questionnaire, the proportion of medium-to-high drug adherence to anti-hypertensive therapy was 89.8% [47].…”
Section: Discussionmentioning
confidence: 99%
“…Volume excess likely accounted for the variation; two studies that used bioimpedance spectroscopy (BIS) as a surrogate of volume excess showed that a fraction of patients with apparent treatment-resistant hypertension had subclinical hypervolemia. 8,10 Because causes of pseudoresistance were not adequately addressed in the existing literature, [7][8][9][10][11] the prevalence of true resistant hypertension among patients on dialysis remains unknown.…”
Section: Ckd-5dmentioning
confidence: 99%
“…The five available studies have provided prevalence rates ranging from 18.0% to 42.0%. [7][8][9][10][11] Several potential explanations exist. These studies used different techniques in the assessment of BP control status (i.e., dialysis unit BP measurement, home BP measurement, or ABPM).…”
Section: Ckd-5dmentioning
confidence: 99%